Developing Framework For A Conceptual Model Towards Assessing The Environmental Compliance Of Non-Residential Building In Jordan - Alawneh, Rami Mohammad Deeb (2019)
Governments across the world have developed strategies to achieve United Nations (UN) Sustainable Development Goals (SDG). Sustainable buildings have significant role towards achieving UN SDGs. Currently, there is lack of information on the subject as none of the existing sustainable building assessment systems describe the relationship between its assessment criteria and UN SDGs. Despite the efforts, non-sustainable building and slow progress towards UN SDGs still prevail in Jordan. Therefore, this research achieved conceptual framework towards efforts to integrate the assessment and management of sustainable non-residential buildings in Jordan with UN SDGs. There are two unanswered questions on how sustainable building contributes to achieve UN SDGs in Jordan and how the contributions of sustainable building towards achieving UN SDGs can be improved. To achieve these two research questions, this research conducted into two main stages, in the first stage, the relationships between the Leadership in Energy and Environmental Design (LEED) v2.2 and the UN SDGs were explored using a quantitative descriptive methodology, because at the time of this research, most certified green buildings in Jordan were under new LEED v2.2 construction. Structured questionnaire surveys were conducted. Pearson‘s Chi-square and frequency tests were carried out to examine these relationships. The results show a positive relationship between LEED v2.2 prerequisites and credits in both WE and EA categories and the UN SDGs 6−9, 12–13, and 15. In the second main stage of this research, a conceptual framework for integrating UN SDGs into sustainable non-residential building assessment and management in Jordan was developed. For this purpose, previous building rating systems were reviewed, the Delphi technique was applied to identify assessment categories and indicators for sustainable non-residential building in Jordan, the Analytic Hierarchy Process (AHP) and Relative Importance Index (RII) methods were applied to develop a new innovative integrated weight (combination of AHP and RII methods) that can maintain the focus of the sustainable building assessment framework on the UN SDGs while solving building sustainability problems according to a country‘s specific context. Additionally, questionnaire surveys were conducted to identify the integration of assessment indicators in project phases and to construct a classification system. Finally, the proposed framework, consist of 12 assessment categories include 75 indicators, was validated by focus group discussion method. The findings in this research can potentially assist in formulating building assessment tools and achieving the UN SDGs in countries other than Jordan.